2002
DOI: 10.1136/adc.87.2.111
|View full text |Cite
|
Sign up to set email alerts
|

The impact of atmospheric pollution on vitamin D status of infants and toddlers in Delhi, India

Abstract: Aims:To compare the vitamin D status of 34 children, 9-24 months old, living in an area of Delhi renowned for high levels of atmospheric pollution (Mori Gate), with a comparable age matched group of children from a less polluted (Gurgaon) area of the city. Methods: Serum concentrations of calcium, alkaline phosphatase (ALP), parathyroid hormone (PTH), 25-hydroxyvitamin D (25(OH)D), and 1,25-dihydroxyvitamin D (1,25(OH) 2 D) were measured. Haze scores, regarded as a surrogate marker of solar UVB radiation reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
2
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(199 citation statements)
references
References 6 publications
6
187
2
4
Order By: Relevance
“…We can also consider that during the winter people use more clothes and do not spend much time outdoors. Another potential factor that could relate to hypovitaminosis D is the air pollution, as previously shown by Agarwal et al 13 . Indeed, São Paulo still presents high concentrations of ozone and other air pollutants.…”
Section: Glycemiamentioning
confidence: 80%
See 1 more Smart Citation
“…We can also consider that during the winter people use more clothes and do not spend much time outdoors. Another potential factor that could relate to hypovitaminosis D is the air pollution, as previously shown by Agarwal et al 13 . Indeed, São Paulo still presents high concentrations of ozone and other air pollutants.…”
Section: Glycemiamentioning
confidence: 80%
“…Indeed, São Paulo still presents high concentrations of ozone and other air pollutants. 13 Unfortunately, we could not evaluate the effects of air pollution in our sample because this would require a control group located in another city in similar latitude, but with a clean air. Other potential confounding factor would be the higher percentage of females in our sample.…”
Section: Glycemiamentioning
confidence: 99%
“…Children may not be exposed to sunlight for lifestyle or cultural reasons. In addition, pollution may decrease the ultraviolet rays reaching the children (Agarwal et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variation in serum 25(OH)D levels, reflected as winter hypovitaminosis D, has been demonstrated in several studies [25,26]. Air pollution probably also plays a role in large cities [27]. Hypovitaminosis D is equally prevalent among rural and urban subjects, [23] but in some studies, urban subjects are found to be more deficient [24,28].…”
Section: Asiamentioning
confidence: 98%